Correlation between obstetric outcome and amniotic fluid index (AFI) in preterm prelabour rupture of membranes (PPROM) - Saraswathy, Anusree; Vaman, Jayshree V.; Brahmanandan, Mayadevi; C., Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The purpose was to determine whether AFI<5 cm after preterm premature rupture of the membranes (PPROM) is associated with an increased risk of maternal and perinatal morbidity. Methods: We performed a prospective case control study of 161 singleton pregnancies complicated by preterm prelabour rupture of the membranes (PPROM) in whom AFI was assessed. Patients were categorized in two groups on the basis of amniotic fluid index- AFI<5 cm or AFI ≥ 5 cm. Categorical data were tested for significance with the χ2 and Fisher exact tests. All 2-sided p values < 0.05 were considered significant. Results: Both groups were similar with respect to selected demographics, gestational age at rupture of the membranes, gestational age at the delivery, birth weight. Both groups were similar with respect to maternal chorio-amnionitis, abruption, mode of delivery, early onset neonatal sepsis and NICU stay. Patients with AFI<5 cm demonstrated greater frequency of C/S delivery for non-reassuring fetal tests. Conclusions: There is no significant difference between obstetric outcome in AFI<5 and AFI> 5 after PPROM between 24- and 37-weeks’ gestation.